ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY - Fariz Amri Ramdhani (2021)
This study is a quantitative study that aims to determine the effect of company size, leverage, audit tenure, type of industry, and the complexity of company operations on audit delay. This study uses data on annual report of finance companies and food and beverage companies listed on Indonesia Stock Exchange. The selection of sample criteria was done by purposive sampling technique with predetermined criteria and data obtained totaling 93 sample data from 31 financial institutions and food and beverage companies. Testing the hypothesis in this study was used Multiple Linear Regression analysis with the SPSS 25 program and a significance level of 5% (0.05). Simultaneously, the results show that company size, leverage, audit tenure, type of industry, and complexity of company operations have a significant effect on audit delay. Partially, the results show that company size has a negative and significant effect on audit delay, while leverage, audit tenure, type of industry, and the complexity of company operations do not have a significant effect on audit delay.